Terrorism today : the past, the players, the future - Spindlove, Jeremy R.; Simonsen, Clifford E. (Boston : Pearson, 2013)
Taking an unbiased approach, Terrorism Today offers a lens into the history and status of terrorism around the world. Written with a global perspective, it addresses different regions of the world and the terrorist groups in each region. The text examines terrorist events and groups, analyzes responses to terrorism and the resulting changes in terrorist strategies, and steps through each continent mapping out current and future trends. The text's fifteen chapters build from historical backgrounds to predictions about terrorism in the twenty-first century.
Part 1: THE DEFINITONS AND HISTORY OF TERRORISM -- 1. In Search of a Definition for Terrorism -- 2. A Brief History of Terrorism -- PART 2: GLOBAL TERRORISM -- 3. The United States of America -- 4. Canada and the Caribbean -- 5. Great Britain and Northern Ireland -- 6. Western Europe -- 7. Eastern Europe and the Balkans -- 8. North Africa and the Middle East -- 9. Persian Gulf -- 10. Northeast, Central, and Southern Africa -- 11. Southern and Southeast Asia -- 12. Pacific Rim -- 13. Latin America and South America -- PART 3: THE WAR ON TERROR -- 14. Countering Terrorism -- 15. The Future-What's Next for Terrorism?
Includes bibliographical references and index.
Keywords: Terrorism; Terrorism -- Prevention; History